2021
DOI: 10.21315/jcdc2021.26.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Privacy in the Relationships between Residential Livability and Residents' Life Satisfaction

Abstract: This article seeks to determine whether privacy has a moderating effect on the relationship between residential livability and life satisfaction among low-income groups in Dutse, Jigawa State, Nigeria. The study utilised a quantitative research design, whereby descriptive and inferential analyses were employed. This was achieved through a wellstructured questionnaire administered to low-cost housing residents in the state. The data were subjected to descriptive analysis using the Statistical Package for Social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In contrast, it is reasonable to presume that those participants who worked in private offices could be at the management level, likely paid a higher salary thus with more resources to navigate life and its challenges, and therefore experiencing a better quality of life (i.e., higher life satisfaction). A couple of studies have also explored the importance of privacy on life satisfaction in both workspaces [59] and residential buildings [60].…”
Section: Job and Life Satisfactionmentioning
confidence: 99%
“…In contrast, it is reasonable to presume that those participants who worked in private offices could be at the management level, likely paid a higher salary thus with more resources to navigate life and its challenges, and therefore experiencing a better quality of life (i.e., higher life satisfaction). A couple of studies have also explored the importance of privacy on life satisfaction in both workspaces [59] and residential buildings [60].…”
Section: Job and Life Satisfactionmentioning
confidence: 99%
“…However, it is important to acknowledge that there are drawbacks to co-living arrangements, one of which is the potential loss of privacy [26,27]. Privacy is considered a crucial element of individuals' quality of life, and the absence of privacy in co-living situations can have a negative impact on residents [27].…”
Section: Related Literaturementioning
confidence: 99%
“…However, it is important to acknowledge that there are drawbacks to co-living arrangements, one of which is the potential loss of privacy [26,27]. Privacy is considered a crucial element of individuals' quality of life, and the absence of privacy in co-living situations can have a negative impact on residents [27]. It is worth noting, however, that the social interactions and support provided within co-living environments may serve as a potential counterbalance to the concerns related to privacy [28,29].…”
Section: Related Literaturementioning
confidence: 99%
“…De Macedo, Ornstein & Elali (2022), for instance, found by a literature review that people's quality of life is related to privacy. Bashari et al (2021) analysed by a structural equation modelling on a questionnaire survey with low-income households in Nigeria, and found a moderating effect of privacy in the residential livability and residents' life satisfaction. In contrast, some studies showed the opposite.…”
Section: Related Literaturementioning
confidence: 99%